Memahami Definisi Riba di Era Modern: Penyuluhan bagi UMKM Industri Pakaian - Athief, Fauzul Hanif Noor; Hakim, Lukmanul; Izzah, Luthfiyyah Nurul (Lembaga penelitian dan pengabdian kepada masyrakat, 2024)
The Elbise Company is a small and medium-sized enterprise (SMEs) in the clothing industry. Due to the majority of its distributor partners being women entrepreneurs, there is limited time available to fulfill their religious knowledge needs. Additionally, Elbise Company had not previously provided specific guidance on the issue of riba (interest). Given this situation, the urgency of providing riba-related training to Elbise's partners has become essential. This activity is conducted periodically, with two sessions, each lasting more than two hours. The guidance is delivered via WhatsApp through text messages. In general, the content covered is divided into two parts: theoretical aspects of riba and common misconceptions prevalent in society. The participants show a high level of enthusiasm during these sessions. This indirectly suggests that there is a strong awareness in the community that the subject of riba is quite complex and that there is an opportunity to provide broader education to the public. Further steps that can be taken include offering personal and continuous mentoring to Elbise's business partners.